Investigation of Stochastic Seismic Response and Index Correlation of an Arch Dam Using Endurance Time Analysis Method - Qiang Xu; Shutong Xu; Jianyun Chen; Jing Li (Advances in Civil Engineering)
The seismic dynamic response and correlation between various indicators of an arch dam under a series of stochastic earthquake excitation are analysed. Seismic response assessment of a concrete arch dam is conducted through nonlinear endurance time analysis (ETA) of a typical arch dam. The 289 m high Baihetan arch dam in Southwest China (as a case study) is subjected to a set of 10 three-component endurance time acceleration histories (ETAHs) synthesised on the basis of the design site acceleration response spectrum to increasing peak ground acceleration (PGA). The effects of dam-reservoir-foundation interaction, radiation damping of infinite rock foundation, and nonlinearities of dam material and joint contact elements are considered. The indices to failure modes of damage propagation through the dam body and the deformation and joint opening beyond the limit states of the arch dam are identified. Dynamic responses, including deformation, joint opening, and damage distribution, are statistically analysed. The dispersion and correlation of indicators are analysed by employing the coefficient of variation and coefficient of correlation, respectively. The deterministic relationships between contraction joint opening, displacement, and damage volume ratio are obtained by using a multivariate fitting method. The results show that those failure indices have similar exponential trends, and seismic intensity parameters exert a significant influence on seismic response and damage under increasing PGA. The results of correlation and fragility analysis demonstrate that damage volume ratio and the sum of joint opening are consistent, which can provide a strong scientific basis for predicting earthquake damage.